(untitled) (Journal of the College of Education for Women, 2019)
The study aimed to get acquainted with kindergarten teachers in the development ofemotional intelligence in children, To achieve this a study too, which consisted of 40 items,within four areas was condncted: (managing emotions, emotional knowledge, empathy, socialnetworking) The study tool was applied to the sample amounting (200) teachers of thekindergarten teachers in the province of Jerash and after analyzing the results statisticallyusing arithmetic averages standard deviations and variance analysis quartet the followingresults were reached :- presence of statistically significant differences at the level of (α =0,05) is attributable to theimpact of the educational level in the areas of empathy and social networking.- The lack of statistical significance at the level (α =0,05) due to the effect of experience inall areas.- The presence of significant differences at the level of (α =0,05) is attributable to the impactof specialization in all areas with the exception of sympathy. The presence of significant differences at the level of (α =0,05) is attributable to the impactof the type of kindergarten in all areas, and the differences were in favor of the privatekindergarten.- There should be emphasis on the role of kindergarten teacher in the development of thecapacities and abilities of children through the media.- Educational and sophisticated programs should be provided in kindergartens to contributeto the development of the child comprehensive and integrated development.- Efforts should be made to develop the teachers constantly whether professionally orcognitively through seminars, lectures, activities, and education and training programs .- There should be a rich learning environment that helps children to integrated development .- Further research should be made in the area of the role of the teachers in the development ofmultiple intelligences among kindergarten children.